2018
DOI: 10.22201/igeof.00167169p.2018.57.4.2104
|View full text |Cite
|
Sign up to set email alerts
|

GA-optimized neural network for forecasting the geomagnetic storm index

Abstract: Se desarrolló un método que combina una red neuronal artificial y un algoritmo genético (ANN+GA) con el fin de pronosticar el índice de tiempo de perturbación de tormenta (Dst). A partir de esta técnica, la ANN fue optimizada por GA para actualizar los pesos de la ANN y para pronosticar el índice Dst a corto plazo de 1 a 6 horas de antelación usando los valores de la serie temporal del índice Dst y del índice de electrojet auroral (AE). La base de datos utilizada contiene 233,760 datos de índices geomagnéticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this situation the Lund operational forecast becomes unreliable, while EDDA still produces valid predictions. Vörös et al (2002) have made the interesting suggestion of using the information about the scaling characteristics of magnetic fluctuations as an additional input to a neural network. They have implemented this by computing the so-called Hölder exponent of past geomagnetic time series and shown that it significantly improved the prediction accuracy.…”
Section: Forecasting D Stmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation the Lund operational forecast becomes unreliable, while EDDA still produces valid predictions. Vörös et al (2002) have made the interesting suggestion of using the information about the scaling characteristics of magnetic fluctuations as an additional input to a neural network. They have implemented this by computing the so-called Hölder exponent of past geomagnetic time series and shown that it significantly improved the prediction accuracy.…”
Section: Forecasting D Stmentioning
confidence: 99%
“…Yet a different method to train a neural network, based on a Genetic Algorithm (GA) has been presented in Vega-Jorquera, Lazzús, and Rojas (2018), where one to six hours ahead predictions were developed using a single hidden layer NN. The results were very good for one hour ahead, but degraded strongly for 6 hours ahead (RM SE ∼ 14).…”
Section: Forecasting D Stmentioning
confidence: 99%